2018
DOI: 10.1016/j.jvs.2017.10.084
|View full text |Cite
|
Sign up to set email alerts
|

Delayed endovascular aortic repair is associated with reduced in-hospital mortality in patients with blunt thoracic aortic injury

Abstract: Consistent with current Society for Vascular Surgery recommendations, more BTAI patients underwent early TEVAR than delayed TEVAR during the study period. However, delayed TEVAR was associated with significantly reduced mortality in this population. Together, these findings support a need for critical appraisal and clarification of existing practice guidelines in management of BTAI. Future studies should seek to understand this survival disparity and to determine optimal selection of patients for early vs dela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
2
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 24 publications
0
32
2
2
Order By: Relevance
“…Some studies have already shown that there is an advantage from late intervention (after 24 hours) in relation to early intervention (in the first 24 hours), even in patients with very severe additional injuries. 18 Marcaccio et al 18 demonstrated in a sample of 507 patients that later intervention was associated with lower mortality rates (5.4%) than early treatment (11.9%). Early intervention was also associated with a higher risk of mortality in a multivariate logistic regression analysis (OR 2.39; 95%CI 1.01-5.67; p = 0.047).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have already shown that there is an advantage from late intervention (after 24 hours) in relation to early intervention (in the first 24 hours), even in patients with very severe additional injuries. 18 Marcaccio et al 18 demonstrated in a sample of 507 patients that later intervention was associated with lower mortality rates (5.4%) than early treatment (11.9%). Early intervention was also associated with a higher risk of mortality in a multivariate logistic regression analysis (OR 2.39; 95%CI 1.01-5.67; p = 0.047).…”
Section: Discussionmentioning
confidence: 99%
“…Although to date there are no randomized and controlled studies comparing endovascular treatment with open surgery for patients with aortic injuries caused by blunt trauma, there has been significant improvement in mortality and morbidity rates as endovascular approaches have replaced conventional open surgery at the majority of trauma centers. 12,18…”
Section: Discussionmentioning
confidence: 99%
“…鈍的外傷による胸部大動脈損傷(blunt thoracic aortic injury: BTAI)は多発外傷の構成要素の一つとなることが多い。BTAIの30–40%はAIS 3以上の外傷を合併するとの報告 1)もあり,しばしば他の損傷と併行した治療を余儀なくされる。BTAIの好発部位は大動脈峡部付近であり 2), 3),ステントグラフト内挿術が治療の第一選択だと近年では明示されるようになった 4), 5), 6), 7), 8)。またBTAIを待機的に治療することの有用性を示す報告も多い 9), 10), 11), 12)。しかし,多発外傷におけるBTAIの治療方針は明確にされておらず,ステントグラフトなどの治療をどのような症例にどのようなタイミングで行うべきか,治療待機期間はどの程度許容されるのかなど,治療方針を決定するには多くの因子を考慮しなければならない。…”
Section: はじめにunclassified
“…Anti Delayed aortic endovascular repair (after the first 24 hours) is usually reserved for high-risk patients with associated traumatic injuries. Recently, many studies have shown a decrease in mortality in BTAI stable patients with delayed repair [14]. The Eastern Association for Surgery of Trauma recommends delayed repair with effective blood pressure control in this subset of patients [4].…”
Section: Medica Therapymentioning
confidence: 99%
“…Management of Grade 3 (moderate injuries) is based on semi-elective repair during the first 24-72 hours along with optimization of blood pressure and prompt initiation of antiplatelet therapy. Emergency thoracic endovascular aneurysm repair (TEVAR) is reserved for severe (Grade 4) injuries [14].…”
Section: Medica Therapymentioning
confidence: 99%